Epidemiological profile of a population living with HIV and features associated to the treatment (Research, Society and Development, 2023)
The prognosis of people living with HIV obtained important progresses in the last two decades. The advent of Antiretroviral Therapy is a factor which provided the increase in life expectancy. However, this expectancy is still smaller than what is observed in the population without the HIV virus. One of the most important parameters to evaluate risks to the population’s health is the analysis of adhesion to the antiretroviral treatment. The objective of this study is outlining an epidemiological profile of a population living with HIV/Aids, relating to possible health risk factors. The research design which was adopted was of cross—sectional descriptive observational character. The convenience sample was 43 PVHIV, serviced at SAE/CTA from Ponta Grossa-PR. Only the variable “family income” presented significant association (p